2021
DOI: 10.1080/13467581.2021.1918553
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal tests investigation into hybrid fiber-reinforce recycled aggregate concrete and convolutional neural network prediction

Abstract: Recycled aggregate concrete (RAC) mixture of hybrid fibers has been proven to be an effective type of hybrid fiber-reinforced recycled aggregate concrete (HyFRAC). To further investigate the engineering potential for HyFRAC, the orthogonal test method was used to do sensibility analysis on the compressive strength and splitting tensile strength of HyFRAC. And a prediction model of compressive strength of HyFRAC based on Convolutional NeuralNetwork (CNN) was proposed. The results show that the ratio of recycled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…When there are many test groups in the whole experiment, selecting representative points from the whole test according to the orthogonality can effectively reduce the number of tests, and the orthogonal experiment is dispersibility and neat comparability. The range and variance was applied to analyze the experimental data; by analyzing the degree of influence of variables on the research object, the best conditions or the best combination can be used to achieve the experimental goals [24][25][26]. In order to study the influence rule of basalt fiber volume rate-V BF (factor A), PVA fiber volume rate-V PF (factor B) and rubber volume rate-V R (factor C) on the compressive strength, splitting tensile strength and flexural strength of HFRC, the L9 (3 3 ) orthogonal experiment scheme was selected, with each factor taking three levels.…”
Section: Experimental Designmentioning
confidence: 99%
“…When there are many test groups in the whole experiment, selecting representative points from the whole test according to the orthogonality can effectively reduce the number of tests, and the orthogonal experiment is dispersibility and neat comparability. The range and variance was applied to analyze the experimental data; by analyzing the degree of influence of variables on the research object, the best conditions or the best combination can be used to achieve the experimental goals [24][25][26]. In order to study the influence rule of basalt fiber volume rate-V BF (factor A), PVA fiber volume rate-V PF (factor B) and rubber volume rate-V R (factor C) on the compressive strength, splitting tensile strength and flexural strength of HFRC, the L9 (3 3 ) orthogonal experiment scheme was selected, with each factor taking three levels.…”
Section: Experimental Designmentioning
confidence: 99%
“…Additionally, other machine learning methods, besides BP neural networks, have demonstrated a favorable trend in predicting the 28-day compressive strength of concrete [38][39][40][41][42]. With the continuous advancement of deep learning, models for predicting the compressive strength of concrete established using CNNs and improved convolutional neural networks exhibit superior predictive performance compared to traditional machine learning methods [43][44][45][46]. This provides novel insights and methods for researching the prediction of compressive strength in pervious concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Concha [25] used a neural network to predict the carbonization depth of recycled-aggregate concrete, and the prediction results showed that the prediction model could provide better prediction results even if there was ambiguity in the data, and the results could be used to evaluate the health status of recycled-aggregate concrete structures. Huang et al [26] used a convolutional neural network (CNN) to predict the compressive strength of mixed-fiber-reinforced recycled-aggregate concrete. The results showed that the CNN prediction model had good prediction accuracy, and the average relative error and maximum relative error of the prediction results were 1.98% and 4.12%, respectively.…”
Section: Introductionmentioning
confidence: 99%